White Spot Syndrome Virus Envelope Protein VP 53 B Functions as a Trypsin Inhibitor and Interacts With Hemocyanin - Wenxu Xia; Lingqi Zhuang; Yuchen Liu; Kai Li; Bing Qin; Shuling Yan; Yongxin Yu; Yongjie Wang (Journal of Fish Diseases, 2026)
White spot syndrome virus (WSSV) remains a persistent and significant threat to the global shrimp aquaculture industry. However, its pathogenic mechanisms remain incompletely understood, and no effective intervention strategies are currently available. In this study, we investigated the functional role of VP53B, an envelope structural protein of WSSV, using a combination of infection bioassays, protein structure prediction, protease inhibition assays and protein binding analyses. Our results demonstrate that VP53B is a critical determinant of per os (oral) infection in shrimp, including Procambarus clarkii (crayfish) and Litopenaeus vannamei (whiteleg shrimp). Functionally, VP53B acts as a trypsin inhibitor and interacts with host hemocyanin. We propose that through modulation of shrimp trypsin and hemocyanin, VP53B disrupts the prophenoloxidase‐activating system, a key innate immune pathway, thereby facilitating successful WSSV infection. This study provides new insights into the molecular mechanisms underlying WSSV oral infectivity and highlights VP53B as a potential target for therapeutic intervention.

Transcriptomic and metabolomic analysis reveals melatonin treatment in delaying postharvest yellowing in broccoli through ABA-pigment metabolism network - Yue Wang; Jianhui Cheng; Wenbo Lei; Shuling Shen; Yan Liu; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2026)

Recent advances in the formation, characterization, and applications of starch-polyphenol complexes: A review - Bo Han; Qianhan Ma; Shuling Yan; Shiyin Jia; Yao Hu; Hao Xu; Siyuan Liu; Hao Zhang; Pengjie Wang; Jiayue Guo (Food Chemistry, 2026)

Enhanced functionality and reduced allergenicity of silkworm pupae protein through Lactiplantibacillus plantarum fermentation - Jing Yang; Shuling Zhou; Yan Chen; Sutee Wangtueai; Jiajia Song (Food Chemistry, 2026)

Herbacetin alleviates acute doxorubicin cardiotoxicity via regulating the ERK1/2-FOXO3a signaling pathway - Sijia Bian; Xinran Li; Peiyan Zhu; Zhiting Jiang; Chen Yan; Shuling Wei; Liqi Luo; Yuhua Zhu; Lan Luo (Human Cell, 2026)

Exogenous melatonin activates BoNAC52-BoRBOHF module and antioxidant system involved in the delay in broccoli yellowing during postharvest - Yue Wang; Lufan Wang; Yuting Li; Wenbo Lei; Jianhui Cheng; Yuan Cheng; Shuling Shen; Lanying Yao; Lichao Zhou; Yan Liu; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2025)

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Effects of high hydrostatic pressure processing on the physicochemical properties, functional characteristics, and antioxidant activity of silkworm pupae protein - Jing Yang; Shuling Zhou; Yan Chen; Jiawang Jin; Jiajia Song (Food Chemistry, 2025)

Application of edible insects to food products: A review on the functionality, bioactivity and digestibility of insect proteins under high-pressure/ultrasound processing - Jing Yang; Yan Chen; Linqing Zhang; Shuling Zhou; Linfeng You; Jiajia Song (Food Chemistry, 2025)

Biochar enhances Cd mineralization through microbially induced carbonate precipitation as a soil remediation strategy for rice paddies - Dinghua Peng; Xianghan Chen; Shuling Zhang; Guoquan Zeng; Chaoqun Yan; Huanyan Luo; Huakang Liu; Heng Xu (Chemosphere, 2024)

Exogenous melatonin delays yellowing in postharvest broccoli by regulation of ABA and carotenoid metabolite - Ran Yan; Mariama Kebbeh; Yuan Cheng; Yue Wang; Yuting Li; Maorun Fu; Yan Liu; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2024)

The virulence plasmid associated with AHPND in shrimp appears to have originated from Vibrio owensii through a process of homologous recombination of parental plasmids and the transposable insertion of two large fragments - Yesheng Yan; Haojie Lu; Xiaosha Liang; Tianqi Xu; Shuling Yan; Yongxin Yu; Yongjie Wang (Journal of Invertebrate Pathology, 2024)

Construction and characterization of egg white protein-gallic acid-xanthan gum-based emulsion and oleogel - Yuzhong Yan; Shuling Chen; Le Deng; Yuxuan Duan; Zhaohua Huang; Deming Gong; Guowen Zhang (Food Hydrocolloids, 2024)

Transcriptomic analysis reveals the role of abscisic acid and ethylene in regulating starch-source biosynthesis associated with soft nose disorder in ‘Keitt’ mango fruit during postharvest - Yuan Cheng; Ying Wang; Lichuan Lou; Yuxuan Wang; Binger Dai; Yue Wang; Mariama Kebbeh; Chen Huan; Shuling Shen; Yan Liu; Xiaolin Zheng; Jeffrey K. Brecht (Postharvest Biology and Technology, 2024)

Effect of heat input on the mechanical properties of welded Q960E ultra-high strength steel butt joints - Shuling Gao; Yanan Yue; Dan Zhang; Ning Li; Yiming Huang; Jiabao Yan; Lijun Yang (Engineering Structures, 2024)

In-depth insight into correlations between gut microbiota and dietary fiber elucidates a dietary causal relationship with host health - Lili Li; Shuling Yan; Shuangjiang Liu; Ping Wang; Wenjun Li; Yuetao Yi; Song Qin (Food Research International, 2023)

Diverse viruses of marine archaea discovered using metagenomics - Yifan Zhou; Liang Zhou; Shuling Yan; Lanming Chen; Mart Krupovic; Yongjie Wang (Environmental Microbiology, 2023)
During the past decade, metagenomics became a method of choice for the discovery of novel viruses. However, host assignment for uncultured viruses remains challenging, especially for archaeal viruses, which are grossly undersampled compared to viruses of bacteria and eukaryotes. Here, we assessed the utility of CRISPR spacer targeting, tRNA gene matching and homology searches for viral signature proteins, such as major capsid proteins, for the assignment of archaeal hosts and validated these approaches on metaviromes from Yangshan Harbor (YSH). We report 35 new genomes of viruses which could be confidently assigned to hosts representing diverse lineages of marine archaea. We show that the archaeal YSH virome is highly diverse, with some viruses enriching the previously described virus groups, such as magroviruses of Marine Group II Archaea (Poseidoniales), and others representing novel groups of marine archaeal viruses. Metagenomic recruitment of Tara Oceans datasets on the YSH viral genomes demonstrated the presence of YSH Poseidoniales and Nitrososphaeria viruses in the global oceans, but also revealed the endemic YSH‐specific viral lineages. Furthermore, our results highlight the relationship between the soil and marine thaumarchaeal viruses. We propose three new families within the class Caudoviricetes for the classification of the five complete viral genomes predicted to replicate in marine Poseidoniales and Nitrososphaeria, two ecologically important and widespread archaeal groups. This study illustrates the utility of viral metagenomics in exploring the archaeal virome and provides new insights into the diversity, distribution and evolution of marine archaeal viruses.

Comparative Study on Added Resistance and Seakeeping Performance of X-Bow and Wave-Piercing Monohull in Regular Head Waves - Shuling Chen; Beilei Zou; Changzhi Han; Shiqiang Yan (Journal of Marine Science and Engineering, 2022)
Bow shape has been recognized as an important factor influencing the seakeeping performance and added resistance of ships. This paper presents a numerical comparative study on added resistance and seakeeping of model ships with ‘X-bow’ and a wave-piercing monohull in regular head waves using a computational fluid dynamics (CFD) software. Different wave heights, wavelengths and forward speeds are considered in the systematic investigation in order to characterize the added resistance and wave-induced motions, and to explore the local wave patterns. The results show a considerably different hydrodynamic characteristic by different bow shapes.

Effect of confining pressure on peak penetration force of the TBM disc cutter - Wu Li; Peng Yan; Ang Lu; Shuling Huang; Wenbo Lu (Arabian Journal of Geosciences, 2022)

Correction to: Complete genome sequence analysis of the Vibrio owensii strain SH‑14 isolated from shrimp with acute hepatopancreatic necrosis disease - Xiaosha Liang; Liang Zhou; Shuling Yan; Yongjie Wang (Archives of Microbiology, 2020)

Complete genome sequence analysis of the Vibrio owensii strain SH-14 isolated from shrimp with acute hepatopancreatic necrosis disease - Xiaosha Liang; Liang Zhou; Shuling Yan; Yongjie Wang (Archives of Microbiology, 2020)

Characterization and prevalence of a novel white spot syndrome viral genotype in naturally infected wild crayfish, Procambarus clarkii, in Shanghai, China - Luzhi Jiang; Jinzhou Xiao; Liyuan Liu; Yingjie Pan; Shuling Yan; Yongjie Wang (VirusDisease, 2017)

Cloning, sequencing and characterization of the genome of a recombinant norovirus of the rare genotype GII.P7/GII.6 in China - Hui Cai; Yongxin Yu; Miao Jin; Yingjie Pan; Shuling Yan; Yongjie Wang (Archives of Virology, 2017)

Prevalence and genomic analysis of infectious hypodermal and hematopoietic necrosis virus (IHHNV) in Litopenaeus vannamei shrimp farmed in Shanghai, China - Chao Chai; Yuchen Liu; Xiaoming Xia; Hongming Wang; Yingjie Pan; Shuling Yan; Yongjie Wang (Archives of Virology, 2016)

Rapid detection of infectious hypodermal and hematopoietic necrosis virus (IHHNV) by real-time, isothermal recombinase polymerase amplification assay - Xiaoming Xia; Yongxin Yu; Linghao Hu; Manfred Weidmann; Yingjie Pan; Shuling Yan; Yongjie Wang (Archives of Virology, 2015)

Genome-wide methylation changes are associated with muscle fiber density and drip loss in male three-yellow chickens - Yonghong Zhang; Jiang Guo; Yan Gao; Shuling Niu; Chun Yang; Chunyan Bai; Xianzhong Yu; Zhihui Zhao (Molecular Biology Reports, 2014)